Bioassay-guided isolation of antimicrobial active alkaloids from Ruta angustifolia (L.) Pers - Mohd Kamal, Laina Zarisa; Mohd Hassan, Norazian; Md Taib, Nurhaya; May Khin, Soe (2010)
Plants of the Rutaceae family are sources of active alkaloids with high potential to defeat microbial infectious diseases and overcome microbial resistance towards antibiotic. The anthranilic acid derived alkaloid especially quinoline, furoquinoline, acridone and 4-quinolone alkaloids are the common types of antimicrobial active alkaloids found in Rutaceae. In this study bioautography-directed fractionation of the crude alkaloidal extract from Ruta angustifolia (L.) Pers. was carried out to focus on the isolation of the antimicrobial active alkaloids. The isolated alkaloids were further identified by spectroscopic method of NMR. The activity of each isolated antimicrobial active alkaloid was quantified by using broth microdilution assay for Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Proteus mirabilis ATCC 25933, Pseudomonas aeruginosa ATCC 27853, Helicobacter pylori ATCC 43504, Enterococcus faecalis ATCC 29212 and Candida albicans ATCC 90028. Two promising antimicrobial alkaloids which are an acridone, arborinine and a 4-quinolone, graveoline were isolated. Arborinine showed an activity against S. aureus, E. coli, P. aeruginosa and C. albicans while graveoline exhibits an activity against all of the bacteria except E. faecalis. MIC values for the two alkaloids against the susceptible microbes ranged between 0.01 mg/mL and 0.025 mg/mL while the MBC values were more than 0.01 mg/mL. These results suggest that the two compounds could be considered as a source of antimicrobial agent which might be studied in more details.